2020
DOI: 10.13057/biodiv/d210311
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric diversity and phenotypic relationship among indigenous buffaloes of Banten, Indonesia

Abstract: Abstract. Murni D, Lestari U, Indriwati SE, Efendi A, Maryani N, Amin M. 2020. Morphometric diversity and phenotypic relationship among indigenous buffaloes of Banten, Indonesia. Biodiversitas 21: 933-940. This study aimed to describe the morphometric diversity and phenotypic relationship among indigenous buffaloes of Banten, Indonesia. In this study, 125 buffaloes from six regions were investigated based on 11 morphometric characters. Morphometric diversity was analyzed using multivariate discriminant analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(40 reference statements)
0
4
1
Order By: Relevance
“…The Euclidean distance among three buffalo subpopulations in Moa Island ranged from 1.84 to 3.87 (Salamena and Papilaja 2010) and imminent to the present study (1.84 to 5.45). Meanwhile, the Euclidean distance among six buffalo subpopulations in the Banten regency ranged from 0.20 to 0.69 (de Melo et al 2018;Konda et al 2019;Murni et al 2020) and lower than the present study. The buffaloes at SK and EK were imminent and caused by an AI program with buffalo bulls from the SK region (called Kalang buffalo).…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…The Euclidean distance among three buffalo subpopulations in Moa Island ranged from 1.84 to 3.87 (Salamena and Papilaja 2010) and imminent to the present study (1.84 to 5.45). Meanwhile, the Euclidean distance among six buffalo subpopulations in the Banten regency ranged from 0.20 to 0.69 (de Melo et al 2018;Konda et al 2019;Murni et al 2020) and lower than the present study. The buffaloes at SK and EK were imminent and caused by an AI program with buffalo bulls from the SK region (called Kalang buffalo).…”
Section: Discussioncontrasting
confidence: 94%
“…In buffalo, the CG measurement has a high correlation with body weight (Dhillod et al 2017;Husni et al 2018;Eriani et al 2019). Murni et al (2020) obtained nine discriminant variables (with five functions) from eleven morphometrical measurements in buffaloes from Banten (Indonesia) with rc value of 0.81 (function 1). Nafiu et al (2015) and Genedy et al (2019) obtained three discriminant variables (with two functions) from seven measurements in buffaloes from Bombana Regency (Indonesia) with RC value of 0.85 (function 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Johari et al (2009), the highest weighting score was for body weight followed by body length, shoulder height, pelvic width, waist width, pelvic circumference, chest circumference, chest depth and chest width in male while in females body weight followed by chest circumference, pelvic width and body length in differentiating swamp buffaloes of three locations. NL was reported to be the most discriminating characteristic being having the highest canonical value (0.996) for function 1 in Banten buffaloes (Murni et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Crossbreeding from far populations will increase diversity compared to crossing individuals from closely populations. Murni et al (2020) reported morphometric diversity and phenotypic relationships of the Buffalo populations in Banten, also related to geographical origins. Baccouche et al (2015), also found three cluster based on HCA analysis of native bovine population in Northen Tunisia, and each cluster consist of animal from different populations.…”
Section: Identification Of Kuantan Cattle Group Using Hierarchical Cl...mentioning
confidence: 97%